2016
DOI: 10.1007/s11356-015-6036-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the novel cis-nitromethylene neonicotinoid insecticide Paichongding on enzyme activities and microorganisms in yellow loam and Huangshi soils

Abstract: Soil enzyme activity and microbial population play important roles in maintaining soil fertility and ensure crop yield. Paichongding (IPP) is a novel cis-nitromethylene neonicotinoid insecticide, which was recently developed in China. In this study, in order to better understand IPP ecological toxicity, the impact of IPP on soil enzyme activity and microbial population in soils was investigated. The results showed that, urease activity was inhibited by IPP before 75 days incubation, after that this inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Another undesirable parameter provided by excessive run-off is the risk of contamination of the soil water and air by pesticides (Pose-Juan et al, 2015). The amount of pesticide that reaches the soil may cause detrimental effects on soil microorganisms and modify the ecosystem (Cai et al, 2016). In this way, the most assertive application techniques of pesticides may reduce environmental problems and consequently, increase the performance of treatments.…”
Section: Spray Retention Studymentioning
confidence: 99%
“…Another undesirable parameter provided by excessive run-off is the risk of contamination of the soil water and air by pesticides (Pose-Juan et al, 2015). The amount of pesticide that reaches the soil may cause detrimental effects on soil microorganisms and modify the ecosystem (Cai et al, 2016). In this way, the most assertive application techniques of pesticides may reduce environmental problems and consequently, increase the performance of treatments.…”
Section: Spray Retention Studymentioning
confidence: 99%
“…IPP is a novel chiral neonicotinoid insecticide with four stereoisomers (RR, SS, RS and SR-IPP) and it was widely used in China for insecticide control in agriculture. Cai et al reported that IPP could decrease soil enzyme activities, change soil microbial population, diversity and composition (Cai et al 2015a(Cai et al , 2016b(Cai et al , 2016c. The activities of microbial protease, catalase, urease and dehydrogenase in soil are both impacted after IPP application in crop (Cai et al 2015a(Cai et al , 2016b(Cai et al , 2016c.…”
Section: Resultsmentioning
confidence: 99%
“…Cai et al reported that IPP could decrease soil enzyme activities, change soil microbial population, diversity and composition (Cai et al 2015a(Cai et al , 2016b(Cai et al , 2016c. The activities of microbial protease, catalase, urease and dehydrogenase in soil are both impacted after IPP application in crop (Cai et al 2015a(Cai et al , 2016b(Cai et al , 2016c. The relative abundance of genus of Bacillus, Pseudomonas, Azohydromonas and Paenibacillus in soils with IPP application increased, the genus of Brevundimonas, Xanthomonadaceae, Massilia, Pedobacter, and Hydrogenophaga were newly appearance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations